2014
DOI: 10.1103/physreve.89.012601
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical heterogeneity in periodically deformed polymer glasses

Abstract: The dynamics of structural relaxation in a model polymer glass subject to spatially homogeneous, time-periodic shear deformation is investigated using molecular dynamics simulations. We study a coarse-grained bead-spring model of short polymer chains below the glass transition temperature. It is found that at small strain amplitudes, the segmental dynamics is nearly reversible over about 10^{4} cycles, while at strain amplitudes above a few percent, polymer chains become fully relaxed after a hundred cycles. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…In this method, the effective distance between two segments of a particle trajectory is computed and then compared with a typical cage size. Similar to the earlier studies [29,31], in our analysis, a cage jump was detected if the effective distance between particle positions before and after the shear transformation is greater than 0.1σ ; otherwise, a particle returned to its cage.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In this method, the effective distance between two segments of a particle trajectory is computed and then compared with a typical cage size. Similar to the earlier studies [29,31], in our analysis, a cage jump was detected if the effective distance between particle positions before and after the shear transformation is greater than 0.1σ ; otherwise, a particle returned to its cage.…”
Section: Resultssupporting
confidence: 86%
“…The mechanical response of amorphous materials to oscillatory shear deformations was recently investigated experimentally [24][25][26][27] and by means of atomistic simulations [28][29][30][31]. It was found that at small strain amplitudes, the amorphous systems gradually settle into dissipative limit cycles where particles are displaced periodically but then return to their original positions [25,28,30].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, reversible avalanches of large particle displacements were observed at strain amplitudes below the critical value [17]. At finite temperatures, it was shown that the mean square displacement of particles exhibits a broad subdiffusive plateau during ten thousand cycles even at small strain amplitudes, and the relaxation process involves intermittent clusters of particles undergoing cage jumps [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It was further shown that over many deformation cycles, the structural relaxation dynamics is spatially and temporally heterogeneous; namely, mobile particles, or cage jumps, tend to aggregate into transient clusters [10,14]. Furthermore, during cyclic shear near the yield strain, a cluster of atoms with large reversible nonaffine displacements induces a long-range, time-dependent elastic field that in turn might trigger secondary structural rearrangements.…”
Section: Introductionmentioning
confidence: 99%